COVID-19 vaccine hesitancy in patients with mental illness: strategies to overcome barriers—a review - Ebrahim Payberah; Daniel Payberah; Ashish Sarangi; Jayasudha Gude (Journal of the Egyptian Public Health Association, 2022)
Abstract Background People with mental health problems are at particular risk both for infection with COVID-19 and for more severe course of illness. Understanding COVID-19 vaccine hesitancy is crucial in promoting vaccine acceptance among people with mental health diagnoses. This review aims to identify the prevalence and discuss factors associated with COVID-19 vaccine hesitancy among the mentally ill population. Main body We conducted a detailed literature search and included 15 articles for discussion in this review. Several studies showed varying trends of vaccine hesitancy rates among different countries. Major factors involved in vaccine hesitancy in general include mistrust, misinformation, believing in conspiracy theories, and negative attitudes towards vaccines. It was surprising that none of the studies were focused on vaccine acceptance rates and factors associated with vaccine hesitancy among the mentally ill population. However, studies do show that COVID-19 is associated with worse healthcare outcomes for psychiatric patients, and vaccine hesitancy correlated with a lower likelihood of receiving mental health treatment and vaccinations. Psychiatrists need to address issues among patients who are particularly vulnerable to the fear of vaccines which include anxiety, panic attacks, certain phobias including trypanophobia and agoraphobia, obsessive-compulsive disorder, and certain types of traumas. Psychiatrists need to communicate effectively, show respect, empathy, and deliver accurate and honest information about the vaccines. Motivational interviewing, getting people with mental health illness to organize vaccine campaigns, and involving families with mental health problems may promote vaccine acceptance among this group. Conclusion Existing literature on the rates of vaccine hesitancy among people with mental health illness is limited. The mental health illness may increase the risk of hesitancy especially in patients having certain emotional disorders such as anxiety and phobia. More studies addressing vaccine hesitancy rates and factors associated with the mentally ill population need to be done in the future.